Multiple Cerebral, Calcified and Infected Hydatid Cysts Case Report and Literature Review - Kisito Kouassi Jean Marie Quenum; Laghmari M; Gana R; Maaqili MR; Bellakhdar F (Journal of Neurological Research And Therapy, 2015)
Calcified and Infected Hydatid Cysts Case Report and Literature Review
Keywords: Hydatid Cysts